2017
DOI: 10.1136/bmjsem-2017-000225
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of alarmins—S100A9, IL-33, HMGB1 and HIF-1α in supraspinatus tendinopathy before and after treatment

Abstract: BackgroundAlarmins, endogenous molecules released on tissue damage have been shown to play an important role in inflammatory musculoskeletal conditions including fracture repair andrheumatoid arthritis. However, the contribution of alarmins to the pathogenesis of tendon disease is not fully understood.MethodsWe investigated expression of alarmin proteins (S100A9, high-mobility group box 1 (HMGB1) and interleukin-33 (IL-33) and hypoxia-inducible factor 1α (HIF-1α), a subunit of an oxygen sensitive transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The tissue and cells derived from tendinopathic and ruptured Achilles tendons show evidence of chronic (non-resolving) inflammation (13). Additional clinical studies support this finding showing enhanced levels of HMGB1 in early stage supraspinatus tendinopathy tissues compared to normal tissues and late stage tendinopathy tissues (37, 38). Moreover, the in vitro study shows that recombinant HMGB1 induces significant inflammatory mediators such as IL-1β, IL-6, IL-33, CCL2, and CXCL-12 (37).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The tissue and cells derived from tendinopathic and ruptured Achilles tendons show evidence of chronic (non-resolving) inflammation (13). Additional clinical studies support this finding showing enhanced levels of HMGB1 in early stage supraspinatus tendinopathy tissues compared to normal tissues and late stage tendinopathy tissues (37, 38). Moreover, the in vitro study shows that recombinant HMGB1 induces significant inflammatory mediators such as IL-1β, IL-6, IL-33, CCL2, and CXCL-12 (37).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, the amplification of the PGE 2 biosynthesis pathway by HMGB1/IL-1β is suggested as an important pathogenic mechanism perpetuating inflammatory and destructive activities in rheumatoid arthritis (51). While it is currently unclear whether our findings will reflect the actual mechanisms of tendinopathy development and treatment in humans, recent studies demonstrated that HMGB1 is present in human tendinopathic tendons and regulates cellular inflammation and protein production in vitro (37, 38). This suggests that HMGB1 plays a similar role in the development of tendinopathy due to mechanical overloading.…”
Section: Discussionmentioning
confidence: 94%
“…In keeping with previous studies, the predominant immune cell sub-types in tendon are monocytes and Tc cells (28). Similarly, immunostaining of diseased human Achilles samples found reduced levels of IL33 compared to healthy or treated patient samples and this was associated with CD68+ macrophages on immuno-flourescence (29). In our study, IL33 expression was predominantly found in clusters containing cells with endothelial gene markers and high surface CD31/ CD34, with little expression in CD68+ clusters or cells expressing collagen genes.…”
Section: Higher Levels Of Col4a1 Krt7 Postn Tagln Thbs1 Timp3 Isupporting
confidence: 90%
“…Recently, there has been increasing evidence documenting the involvement of HMGB1 in musculoskeletal disease 23‐27 . These studies suggest diverse biological functions of HMGB1, including the involvement in both promotion of inflammation and tissue repair 15,23,24,27 . To our knowledge, no reviews have compared the role of HMGB1 in different musculoskeletal diseases.…”
Section: Introductionmentioning
confidence: 99%